158k views
5 votes
Let f(k) = 7k6 + 6k - 10 and g(k) = -366 - 7k + 1. Find the difference (f - g)(k).

User DaveRandom
by
5.4k points

1 Answer

3 votes

Correct question is;

Let f(k) = 7k^(6) + 6k - 10 and g(k) = -3k^(6) - 7k + 1. Find the difference (f - g)(k).

Answer:

(f - g)(k) = 10k^(6) + 13k - 9

Explanation:

We are given;

f(k) = 7k^(6) + 6k - 10

g(k) = -3k^(6) - 7k + 1

Thus;

(f - g)(k) = 7k^(6) + 6k - 10 - ( -3k^(6) - 7k + 1)

(f - g)(k) = 7k^(6) + 6k - 10 + 3k^(6) + 7k - 1)

(f - g)(k) = 10k^(6) + 13k - 9

User Franco Roura
by
5.5k points